COMPARISON OF VARIOUS FEED SAMPLES PREPARATION METHOD FOR IN VITRO GAS TEST - Kustantinah, Kustantinah (2008)
Fersh, freeze-dried and oven-dried samples of the leaves from seven plants species (Native grass, Imperata cylindrica, Pennisetum hybrid, Ceiba petandra, Musa sp, Leucaena leucocephala, and Dalbergia latifolia) taken from Yogyakarta, Indonesia were used to evaluate in vitro gas production in the absence or presence of polyethylene glycol (PEG). The nutritive value was assessed using the in vitro gas production technique after incubation for 3, 6, 12, 24, 48, 72, and 96h. The volume of gases produced from samples ranged from 25.33 to 68.51 ml in the absence of PEG, and from 29.38 to 75.99 ml in the presence of PEG. There was no responce of PEG for the grass. The fractional rate of gas production from samples that without or added with PEG varied between 1.10 to 4.80% and 1.20 to 4.80%, respectively. The mean value of gas production from fresh samples blend in 1 minutes and 2 minutes both higher significantly (P<0.05) than from freeze-dried and oven-dried samples. Fresh samples blended in 1 minutes produced a higher volume of gas than oven-dried samples but not significant. The mean value of gas production from samples that added with PEG higher significantly (P<0.05) than without PEG.